Technology on a lease: keeping pace while reining in finances. - Castleton, Ron; Petreshock, Cindi (American City & County, 1997)
Renting and leasing allow city and county governments to meet their equipment needs while conserving valuable capital and keeping pace with rapid technological advances. Outright purchases can drain available funds, limiting overall buying power. Many financial institutions are now offering flexible and easily administered leasing and rental programs that provide governments with the means to better serve their populations.